The Transition Mechanism and Revitalization Path of Rural Industrial Land from a Spatial Governance Perspective: The Case of Shunde District, China - Lianma Zhang; Dazhuan Ge; Pan Sun; Dongqi Sun (Land, 2021)
The transition of rural industrial land has a critical role to play in rural revitalization. The study of rural spatial governance is an important starting point for analyzing the processes and exploring the paths through which the transition of rural industrial land takes place. This study takes the case of Shunde District, China, a typical semi-urbanized area, as its research object and constructs an analytical framework for rural industrial land transition based on spatial governance; it uses this case to conduct an analysis of the spatiotemporal processes and dilemmas involved in rural industrial land transition. Hengding Industrial Park is taken as a specific example to study how the processes and mechanisms involved in the transition of rural industrial land work in practice from a spatial governance perspective, and the path of rural revitalization based on rural spatial governance is discussed. The conclusions are as follows: (1) the fragmentation of rural space, the difficulty of renewing rural industrial land, the chaos of ownership, and the incomplete mechanism of the differentiation and game of multiple subjects, are the main obstacles in the process of rural industrial land transition in Shunde District; (2) since the 1990s, the rural industrial land dominant morphology—including quantity, structure, and so on—and the recessive morphology, including property rights, organizational systems, and input–output efficiency, have all undergone significant changes; (3) the comprehensive governance of rural space under the analytical framework of “matter-ownership-organization,” is an important starting point for analyzing the process of transition of rural industrial land. The “top-down” and “bottom-up” approaches, combining rural spatial governance strategy and the effective participation of multiple subjects, are important means of promoting the transition of rural industrial land; (4) rural spatial governance is conducive to promoting the transition of rural land use and the healthy development of rural space. The experience of semi-urbanized regions with rural revitalization is of vital significance for other regions.